The Berenstain Bears think of those in need - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 1999)
When Mama Bear decides that the family has accumulated too many old toys, books, and games, they sort through all their extra stuff and take it to the Old Bears Home, the Beartown Children's Hospital, and the Bears-Who-Care store.
Accelerated Reader AR
Keywords: Charity -- Juvenile fiction; Charity -- Fiction; Bears -- Fiction